Biophysical Screening of a Focused Library for the Discovery of CYP121 Inhibitors as Novel Antimycobacterials. (26th September 2017) - Brengel, Christian; Thomann, Andreas; Schifrin, Alexander; Allegretta, Giuseppe; Kamal, Ahmed A. M.; Haupenthal, Jörg; Schnorr, Isabell; Cho, Sang Hyun; Franzblau, Scott G.; Empting, Martin; Eberhard, Jens; Hartmann, Rolf W.
Abstract: The development of novel antimycobacterial agents against Mycobacterium tuberculosis (Mtb) is urgently required due to the appearance of multidrug resistance (MDR) combined with complicated long‐term treatment. CYP121 was shown to be a promising novel target for inhibition of mycobacterial growth. In this study, we describe the rational discovery of new CYP121 inhibitors by a systematic screening based on biophysical and microbiological methods. The best hits originating from only one structural class gave initial information about molecular motifs required for binding and activity. The initial screening procedure was followed by mode‐of‐action studies and further biological characterizations. The results demonstrate superior antimycobacterial efficacy and a decreased toxicity profile of our frontrunner compound relative to the reference compound econazole. Due to its low molecular weight, promising biological profile, and physicochemical properties, this compound is an excellent starting point for further rational optimization. Abstract : A new anti‐TB arsenal : This study describes the discovery of new inhibitors of CYP121 from M. tuberculosis by a systematic screening of a focused P450 inhibitor library combining surface plasmon resonance spectroscopy and a heme coordination assay. Further biological characterizations and mode‐of‐action studies resulted in a frontrunner compound with superior antimycobacterial efficacy and a decreased toxicity profile relative to the reference compound econazole.